INNOVATION MANAGEMENT: A SYSTEMATIC LITERATURE ANALYSIS OF THE INNOVATION MANAGEMENT EVOLUTION - Ana Paula Vilas Boas Viveiros Lopes; Kumiko Oshio Kissimoto; Mario Sergio Salerno; Marly Monteiro de Carvalho; Fernando José Barbin Laurindo (Brazilian Journal of Operations & Production Management, 2016)
Innovation management has been received increasing attention in the operations management field during the last years. Academics and managers have long been discussing the innovation nature and its importance for the organization’s growth and competitive advantage. However, one issue that remains unclear is how to recognize what type of innovation management is necessary for each company or situation. One of the reasons for this issue is the different dimensions to which innovation can be addressed – technological, organizational, process and product, among others. Moreover, the differences between incremental and disruptive innovation lead to different ways of management. This paper examines the literature on innovation management in the last 38 years (1975 – 2013) aiming at identify and classify innovation management models. The methodological approach encompasses bibliometric and content analysis. The results show seven models’ categories: project management, organizational strategy, knowledge management, product management, types of innovation, technological innovation, and open innovation.